Severe Symptomatic Primary CMV Infection in Inflammatory Bowel Disease Patients with Low Population Seroprevalence - Catherine Rowan; Ciaran Judge; Mary D. Cannon; Garret Cullen; Hugh E. Mulcahy; Elizabeth Ryan; Cillian F. De Gascun; Glen A. Doherty (Gastroenterology Research and Practice)
Background. Cytomegalovirus disease in patients with inflammatory bowel disease is frequently the result of viral reactivation. Conversely, primary CMV infection is believed to be uncommon in immunocompetent adults due to high population seroprevalence. Objectives. The aim of this study was to examine the frequency and severity of primary cytomegalovirus infection in an adult cohort of IBD patients. Study Design. A retrospective review of a prospectively maintained database of 3200 IBD patients attending a single academic centre was performed. Patients with primary CMV infection 2010–13 were identified; clinical, serologic, and virologic parameters were studied in detail. The seroprevalence of CMV in the patient population was also evaluated. Results. Eight patients with IBD (UC = 3, IBD-U = 1, CD = 4) presented with primary CMV infection. Patients presented with both gastrointestinal and extraintestinal symptoms. Mean age was 33 years, and median duration of disease was 72 months. All eight patients were receiving a thiopurine immunomodulator. Median duration of IM use was 144 weeks (range 7–720 weeks). All 8 patients required hospitalisation, with 1 ICU admission; the median length of hospital stay was 11 days (range 6–27). Infection resolved in all cases with withdrawal of immunomodulator and/or antiviral therapy. Seroprevalence of IgG to CMV, indicating prior exposure, in a subgroup of IBD patients (n=80) was 30.5% and increased with age. Conclusion. Primary cytomegalovirus infection can cause a severe illness in IBD patients, particularly those receiving immunosuppression. In areas where adult CMV seroprevalence is low, evidence of CMV should be sought in IBD patients presenting with any febrile systemic illness.